Influence of Student Behavior on Hepatitis A Incidence and Prevalence in Islamic Boarding School âSidogiriâ - Secaria, Bhirawa Odie Prino; Sulistyorini, Lilis; Keman, Soedjajadi (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
abstract